2015
DOI: 10.1039/c4ta06688j
|View full text |Cite
|
Sign up to set email alerts
|

O3–NaxMn1/3Fe2/3O2as a positive electrode material for Na-ion batteries: structural evolutions and redox mechanisms upon Na+(de)intercalation

Abstract: International audienceThe electrochemical properties of the O3-type NaxMn1/3Fe2/3O2 (x = 0.77) phase used as positive electrode material in Na batteries were investigated in the 1.5–3.8 V, 1.5–4.0 V and 1.5–4.3 V ranges. We show that cycling the Na cells in a wider voltage range do not induce a significant gain on long term cycling as the discharge capacities reached for the three experiments are identical after the 14th cycle. The structural changes the material undergoes from 1.5 V (fully intercalated state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 61 publications
4
94
1
Order By: Relevance
“…2), D-Na x RuO 3 undergoes a structural change from O3 to P3 (with Na in prismatic sites owing to the ABBCCA oxide-ion stacking) on charging23. This O3→P3 transition is commonly observed in O3-NaMO 2 materials through gliding of the [Na 1/3 Ru 2/3 ]O 2 slabs from ABCABC (O3) to ABBCCA (P3) stacking925. The synchrotron XRD pattern of the charged state (D-Na 1 RuO 3 ; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2), D-Na x RuO 3 undergoes a structural change from O3 to P3 (with Na in prismatic sites owing to the ABBCCA oxide-ion stacking) on charging23. This O3→P3 transition is commonly observed in O3-NaMO 2 materials through gliding of the [Na 1/3 Ru 2/3 ]O 2 slabs from ABCABC (O3) to ABBCCA (P3) stacking925. The synchrotron XRD pattern of the charged state (D-Na 1 RuO 3 ; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Transitions from one stacking to another are possible through slab gliding requiring only small atomic displacement and no breaking of M-O bonds. They can therefore occur at room temperature during the cycling of the battery 29,30,39,40 , as it was more recently shown in the O3-NaxMn1/3Fe2/3O2 system 41 . This difference in stacking arrangements leads to a significant change in intensity ratio between the reflections 104h and 105h in the Xray diffraction patterns indexed with an undistorted hexagonal cell.…”
Section: Evolution Of the Cell Parameters And Stackingmentioning
confidence: 94%
“…Specially, a small amount of the O3 type could not completely transform to P3 but always involve in the electrochemical process. [171,172] Sharma et al reported that O3-Na 2/3 [Fe 2/3 Mn 1/3 ]O 2 undergoes a series of twophase and solid-solution reactions leading to a disordered phase at the charged state before undergoing solid solution and two behavior on discharge, but the structural motif and the space group are preserved. [173,174] The physical origin of bistability and differences in Na ion diffusion between P2 and O3 phases may result from the electrostatic interactions within oxide layers which control the bistable nature of these two phases.…”
Section: Fe/mn-based Oxidesmentioning
confidence: 99%